PELINDUNGAN HUKUM ATAS KARYA ILMIAH DARI TINDAKAN PLAGIAT MENURUT PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU - Huller Gabe Dimpos Sinaga; Runtung Sitepu; Keizerina Devi Azwar; Dedi Harianto (USU LAW JOURNAL, 2017)
ABSTRACT Criteria declared that plagiarism is plagiarism made against creative works protected by copyright laws, it can be proven the existence of an element of the copy or imitate creation, it can be proven that the act of copying or imitating creation. Plagiarism in college are liable to imprisonment and/ or fined. In addition to criminal sanctions, perpetrators of plagiarism committed by students will be subject to cancellation diplomas to students who committed plagiarism. The law provides legal protection which the copyright holder/ creator can apply for compensation for the occurrence of plagiarism and asked for the seizure of the objects that were announced or propagated creation. Law on National Education System provides legal protection form by giving administrative sanction of revocation of a degree, criminal penalties of imprisonment and fines for perpetrators of plagiarism. Law on Teachers and Lecturers, and the National  Education Minister Regulation No. 17 Year 2010 on the Prevention and Combating Plagiarism in Higher Education provides legal protection scientific work universities. Forms of legal protection against the scientific work is to impose administrative sanctions in the form of cancellation and revocation degree diplomas to students, lecturers, researchers who committed plagiarism. Keywords: scientific papers copyright, plagiarism, legal protection